Real-world evidence of the effects of sodium-glucose co-transporter 2 inhibitors on the dosing of diuretics in patients with heart failure: a retrospective cohort study - Alsalem, Abdulaziz; Alsultan, Mohammed M.; Alqarni, Faisal; Almangour, Abdullah; Alsharekh, Lolwa; Alenazi, Saleem; Alzahrani, Saleh; Almanqour, Raghad A.; Alazmi, Abdullah; Alzahrani, Abdullah (Frontiers in Pharmacology, 2024)
Background: Heart failure (HF) was estimated to impact approximately 64 million individuals worldwide in 2017 and is predicted to rise in the coming years. Therefore, the aim of our study was to evaluate the effects of sodium-glucose transport protein 2 (SGLT2) inhibitors on the dosing of diuretics among individuals diagnosed with HF. Methods: A retrospective cohort study was conducted at Security Forces Hospital in Riyadh, Saudi Arabia, between January 2018 and August 2022. The study included adult patients who were diagnosed with heart failure and received dapagliflozin and/or diuretic. A descriptive analysis was conducted to identify significant differences between both groups by using the chi-square test for categorical variables and the Student’s t-test for continuous variables. A logistic regression model was also run to identify the odds of each event. Statistical significance was indicated by p values less than .05. Results: Overall reduction in diuretics was reported in 68 patients in the SGLT2 inhibitors plus diuretic therapy group, while in the diuretic therapy group 25 patients reported overall reduction in diuretics (OR = 4.81, 95% [2.74–8.45]). The reduction of the loop dose level was reported by 58 patients in the SGLT2 inhibitors plus diuretic group and by 25 patients in the diuretic group (OR = 3.48, 95% [1.98–6.11]). The discontinuation of thiazide was reported by 16 patients in the SGLT2 inhibitors plus diuretic therapy group, but by only two patients in the diuretic group (OR = 9.04, 95% [2.03–40.19]). After 6 months, ejection fraction was increased by 2.74 in the SGLT2 inhibitors plus diuretic group (p = .0019) and decreased by 2.56 in the diuretic group (p = .0485), both of which were statistically significant. The mean dose changes were decreased by 14.52 in the SGLT2 inhibitors plus diuretic group (p < .0001), which was statistically significant. Conclusion: Treatment with SGLT2 inhibitors plus diuretic significantly reduced the patients’ diuretic requirements. Therefore, our finding supports the theoretical concept of minimizing the level of diuretic upon the initiation of SGLT2 inhibitors.